2009
DOI: 10.1021/jp9012653
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Molecular Level of Polyimide-Based Solvent Resistant Nanofiltration Membranes with Positron Annihilation Spectroscopy

Abstract: Positron annihilation spectroscopy (PAS) has been performed to link fundamental polymer properties to membrane performance, more specifically for polyimide (PI)-based solvent-resistant nanofiltration membranes. Laboratory-made membranes with well-known properties were applied first to define proper pretreatment conditions for the membrane to allow PAS-analysis and to allow more correct linking of PAS results to membrane properties. This knowledge was then applied to probe the structure of commercial PI-based S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 24 publications
(30 reference statements)
1
25
0
Order By: Relevance
“…In general, the retention performance of NF membranes is mainly governed by the mean size of free volume elements or ''nanopores'', while the liquid transport is also determined by the fraction of free volume elements and its interconnectivity. By using different experimental techniques including solute retention [5,6], liquid-liquid displacement porosimetry [6], atomic force microscopy (AFM) [5][6][7][8][9][10], positron annihilation lifetime spectroscopy (PALS) [10][11][12], and combination of transmission electron microscope (TEM) with high contrasts like OsO 2 [13,14], the mean size of free volume elements or ''nanopores'' of different NF membranes for both aqueous and non-aqueous applications can be estimated to be at the level of about 0.4-2 nm; the estimated ''pore'' size distribution for the selective layer is relatively well correlated with the nanofiltration performance of the membranes. However, such porosity has little in common with the porosity of conventional microporous adsorbents such as alumina, silica, and carbon molecular sieves.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the retention performance of NF membranes is mainly governed by the mean size of free volume elements or ''nanopores'', while the liquid transport is also determined by the fraction of free volume elements and its interconnectivity. By using different experimental techniques including solute retention [5,6], liquid-liquid displacement porosimetry [6], atomic force microscopy (AFM) [5][6][7][8][9][10], positron annihilation lifetime spectroscopy (PALS) [10][11][12], and combination of transmission electron microscope (TEM) with high contrasts like OsO 2 [13,14], the mean size of free volume elements or ''nanopores'' of different NF membranes for both aqueous and non-aqueous applications can be estimated to be at the level of about 0.4-2 nm; the estimated ''pore'' size distribution for the selective layer is relatively well correlated with the nanofiltration performance of the membranes. However, such porosity has little in common with the porosity of conventional microporous adsorbents such as alumina, silica, and carbon molecular sieves.…”
Section: Introductionmentioning
confidence: 99%
“…Positron lifetime technique is well documented as a powerful tool for examining the hole structure of functional materials. [9][10][11] Some positrons implanted into polymer may combine with one of the spur electrons to form positronium (Ps: the hydrogen-like state of a positron and an electron). In free space, spin-parallel triplet ortho-Ps (o-Ps) annihilates with an intrinsic lifetime of 142 ns, while spin-antiparallel singlet para-Ps (p-Ps) annihilates with a shorter lifetime of 125 ps.…”
Section: Positron Resultsmentioning
confidence: 99%
“…9 shows representative views of the membranes prepared from compositions containing 18 wt%, 20 wt% and 22 wt% PI, together with a magnification of the top layer. It is not clear from these SEM pictures whether the increased rejection and decreased permeance are due to a densification of the skin layer [35,36]. However, the macrovoids are smaller at higher polymer concentration.…”
Section: Permeance (L M -2 Bar -1 H -1 )mentioning
confidence: 92%
“…at the level of the free volume between the polymer chains. This free volume in PI-membranes has been investigated in the past using positron annihilation lifetime spectroscopy (PALS) [31,32]. This showed that the free volume in the toplayer indeed increases towards the more open sublayer, although this cannot be seen on SEM pictures.…”
Section: Comparison Between Post and Simmentioning
confidence: 99%